Dams 2000 proceedings of the biennial conference of the BDS held at the University of Bath on 14-17 June 2000 - Tedd, P. (Thomas Telford, 2000)
This volume presents the proceedings of Dams 2000, the 11th conference of the British Dam Society, and brings together a valuable collection of 38 papers covering a wide variety of topics related to reservoir safety and the rehabilitation of existing dams. Many of the papers are case histories describing investigations and rehabilitation of existing dams to extend asset life.
Keywords: Dams -- Great Britain -- Congresses.; Dams -- Great Britain -- Design and construction -- Congresses.; Dams -- Great Britain -- Safety measures -- Congresses.; elektronické knihy; electronic books